2006
DOI: 10.1002/ijc.21684
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a monoclonal anti‐phosphatidylserine antibody with gemcitabine strongly inhibits the growth and metastasis of orthotopic pancreatic tumors in mice

Abstract: Pancreatic cancer continues to have a dismal prognosis and novel therapy is needed. In this study, we evaluate a promising new target for therapy, phosphatidylserine (PS). PS is an anionic phospholipid located normally on the inner leaflet of the plasma membrane in mammalian cells. In the tumor microenvironment, PS becomes externalized on vascular endothelium. The monoclonal antibody 3G4 binds PS and promotes an inflammatory response against tumor blood vessels, resulting in reduction of tumor growth. Mice wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 18 publications
4
64
0
Order By: Relevance
“…It has been shown that 2aG4 treatment not only has an antivascular action when combined with irradiation in this model, but also enhances the immunogenicity of the tumour leading to immunologic control of residual tumour cells. Moreover, antivascular effects and antitumour effects were accompanied by the recruitment of host immune cells in tumour vasculature and the subsequent infiltration into the tumour interstitium, as shown also by other studies (Beck, 2006;Tozer, 2008).…”
Section: Combination Therapy Involving Vascular Disrupting Agents (Vdas)supporting
confidence: 74%
See 3 more Smart Citations
“…It has been shown that 2aG4 treatment not only has an antivascular action when combined with irradiation in this model, but also enhances the immunogenicity of the tumour leading to immunologic control of residual tumour cells. Moreover, antivascular effects and antitumour effects were accompanied by the recruitment of host immune cells in tumour vasculature and the subsequent infiltration into the tumour interstitium, as shown also by other studies (Beck, 2006;Tozer, 2008).…”
Section: Combination Therapy Involving Vascular Disrupting Agents (Vdas)supporting
confidence: 74%
“…It has been shown that 2aG4 treatment not only has an antivascular action when combined with irradiation in this model, but also enhances the immunogenicity of the tumour leading to immunologic control of residual tumour cells. Moreover, antivascular effects and antitumour effects were accompanied by the recruitment of host immune cells in tumour vasculature and the subsequent infiltration into the tumour interstitium, as shown also by other studies (Beck, 2006;Tozer, 2008).To this regard, we evaluated a successful combination strategy in neuroblastoma model using liposomal formulations of DXR targeted against both tumour cells, via anti-GD 2 monoclonal antibodies, and against the tumour vasculature, via the NGR peptide (Pastorino, 2006). The anti-GD 2 -targeted liposomes resulted in direct cell kill, including cytotoxicity against cells that were at the tumour periphery and were independent of the tumour vasculature, whereas NGR peptide-targeted liposomal doxorubicin bind to and killed angiogenic blood vessels and, indirectly, the tumour cells that these vessels supported, mainly in the tumour core.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…The murine (Pan02) and human (MiaPaca-2) pancreatic adenocarcinoma cell lines were obtained from the Developmental Therapeutics Program (Division of Cancer Treatment and Diagnosis, National Cancer Institute, Frederick, MD) and the American Type Culture Collection (Manassas, VA), respectively, and maintained as described (21). The mAbs MJ7/18 (22), AFRC Mac 48 (Mac 48, a rat IgG2a specific for phytochrome; European Collection of Animal Cell Cultures, Salisbury, United Kingdom), 9G10 (23) C44, 2C3, and Gv39M (20, 23 -25) were purified from hybridoma supernatant by protein A or G affinity chromatography.…”
Section: Methodsmentioning
confidence: 99%